2020
DOI: 10.3390/ma13143118
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fibroblast Metabolic Activity of Collagen Scaffolds via the Addition of Propolis Nanoparticles

Abstract: Propolis natural extracts have been used since ancient times due to their antioxidant, anti-inflammatory, antiviral, and antimicrobial activities. In this study, we produced scaffolds of type I collagen, extracted from Wistar Hanover rat tail tendons, and impregnated them with propolis nanoparticles (NPs) for applications in regenerative medicine. Our results show that the impregnation of propolis NPs to collagen scaffolds affected the collagen denaturation temperature and tensile strength. The changes in stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…They reported that despite the capillary increase in the healing tissue, they did not observe a significant difference compared to the control group. González-Masís et al[ 22 ] adsorbed propolis into scaffolds consisting of collagen extracted as nanoparticles from rat tails. They showed that propolis increased the denaturation temperature and tensile strength of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that despite the capillary increase in the healing tissue, they did not observe a significant difference compared to the control group. González-Masís et al[ 22 ] adsorbed propolis into scaffolds consisting of collagen extracted as nanoparticles from rat tails. They showed that propolis increased the denaturation temperature and tensile strength of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Within its self-assembly, the properties of a collagen scaffold, in particular collagen denaturation and tensile strength, can be reduced by impregnation and following deposition on fibrils of propolis nanoparticles [ 68 ]. At 100 μg/mL, the propolis obtained from Apis mellifera maintained the fibril structure of collagen extracted from rat tail and enabled the culture of fibroblast cell line, by providing cells a metabolic stimulus, likely activating their proliferation.…”
Section: Scaffold Design and Experimental Studiesmentioning
confidence: 99%
“…Natural polymers such as chitosan, gelatin, collagen, and cellulose have been widely used for biomedical applications as ECM due to their great biocompatibility and bioactivity. However, their main limitations are related to batch variability and unsuitable physicochemical properties for certain manufacturing processes [49][50][51][52].…”
Section: Thermo-responsive Smart Polymersmentioning
confidence: 99%